Decreased Expression of Negative Immune Checkpoint VISTA by CD4+ T Cells Facilitates T Helper 1, T Helper 17, and T Follicular Helper Lineage Differentiation in GCA - Hid Cadena, Rebeca; Reitsema, Rosanne D.; Huitema, Minke G.; van Sleen, Yannick; van der Geest, Kornelis S. M.; Heeringa, Peter; Boots, Annemieke M. H.; Abdulahad, Wayel H.; Brouwer, Elisabeth (Frontiers in Immunology, 2019)
Loss of immune checkpoint (IC) Programmed Death-1 (PD-1) and PD-Ligand1 (PD-L1) expression has been implicated in the immunopathology of Giant Cell Arteritis (GCA). The contribution of the negative immune checkpoint V-domain Immunoglobulin-containing suppressor of T cell activation (VISTA) to GCA pathology has not yet been studied. The aim of our study was to investigate if expression of VISTA and other IC molecules by peripheral blood (PB) immune cells is modulated in GCA and at the site of vascular inflammation. In addition, we assessed the effect of VISTA-Ig engagement on in vitro CD4+ T helper (Th) lineage differentiation. To this end, frequencies of monocytes expressing CD80/86, PD-L1, PD-L2 and VISTA were determined in blood samples from 30 GCA patients and 18 matched healthy controls by flow cytometry. In parallel, frequencies of CD4+ cells expressing CD28, Cytotoxic T-Lymphocyte-associated antigen-4 (CTLA-4), PD-1, and VISTA were determined. Immunohistochemistry was employed to detect VISTA, PD-1 and PD-L1-expressing cells in temporal artery biopsies (TAB) diagnostic of GCA. Furthermore, the effect of VISTA-Ig on in vitro CD4+ Th lineage differentiation in patients and controls was determined. Our study shows that frequencies of CD80/CD86+ and VISTA+ monocytes were decreased in treated GCA patients only. Moreover, proportions of PD-1+ and VISTA+ Th cells were significantly decreased in GCA patients. Clear infiltration of VISTA+, PD1+ and PD-L1+ cells was seen in GCA TABs. Finally, VISTA-Ig engagement failed to suppress Th1, Th17 and Tfh lineage development in GCA. Our results indicate that decreased expression of VISTA may facilitate development of pathogenic Th1 and Th17 cells in GCA.